Metode Pengajaran Bahasa Arab Tradisional Dan Modern - Kalimatun Nabil, Muaz; Abidin, Zainul; Hakami, Fauzan (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2024)
This study compares traditional and modern learning methods to identify their advantages, disadvantages, and effectiveness on the teaching-learning process. Traditional methods such as qawaid and rote memorization emphasize teacher authority and one-way knowledge, while modern methods such as project-based learning and the use of digital technology emphasize students' active participation and critical thinking skills. A qualitative approach with literature analysis and literature studies suggests that ancient methods are relevant for understanding basic concepts but less effective in developing cognitive and analytical skills. In contrast, modern methods increase student engagement and skills that match the needs of the times. In conclusion, the integration of ancient and modern methods can create a more holistic and adaptive learning environment, leveraging the advantages of both approaches to meet the needs of individual students.